Total physical response (TPR) storytelling as a strategy for teaching english as a foreign language to pre-school children (ages 4 to 5) - Rodas Reinbach, Diana Lee
The main goal of the present research Project was to analyze the effectiveness of Total Physical Response Storytelling (TPRS) as a methodology for teaching English as a foreign language to Pre-school children. After investigating the different language teaching approaches and the developmental features of children within the ages of 3 and 5, as well as the motivations to begin English teaching at an early age, the method was applied to a group of 13 children from Pre-school level, in 18 sessions over a period of three months. The method focused on developing children?s oral skills through Total Physical Response (TPR) activities, Storytelling and other child-appropriate tasks, such as songs, chants, games, arts and crafts. The study focused on investigating the effectiveness of TPRS for oral skills acquisition and vocabulary development in English as a foreign language by providing sufficient comprehensible input through interesting and engaging activities. It is based on the idea that language is acquired in a natural way when the student understands the information and is interested in it. The results during the 18 sessions and in the final evaluation revealed the positive effects of TPRS, which is why this approach can be considered as an alternative tool to teach English as a foreign language, especially to young learners due to its dynamic and appealing activities.